CASE RECORD OF NIFUROXASID WITHIN THE ERADICATION THERAPY SCHEME OF H. PYLORI - P.L. Shcherbakov; A.S. Potapov; Ye.S. Dublina; M.Yu. Shcherbakova; G.A. Samsygina; S.I. Erdes; A.I. Logvinova; L.V. Kudruvtseva ("Paediatrician" Publishers LLC, 2006)
(Voprosy sovremennoi pediatrii = Current pediatrics. 2006;5(5):102-103)